Using structural equation modelling to reassess bias in judging the vault event in men’s artistic gymnastics - Sai-fu Fung; Yoon-Soo Han; Arturs Mickevics (Scientific Reports)
Abstract In gymnastics competitions, the judges evaluate the performance of the gymnasts to determine the winners. Over the past few decades, cognitive psychology scholars have argued that judges in international gymnastics competitions may possess national biases and various forms of memory bias. This paper newly evaluates these biases using empirical data obtained from the men’s vault qualification event in the 51st FIG Artistic Gymnastics World Championships Liverpool – 2022. The data consisted of all of the Men’s Artistic Gymnastics (MAG) vault scores in the qualification round (N = 133), collected from seven execution panel judges representing Argentina, Colombia, Kazakhstan, Norway, the People’s Republic of China, the Republic of Korea, and Slovenia. These scores were analysed using the structural equation modelling (SEM) technique. The SEM results indicated good model fit, χ2 (14.404) / 12 = 0.83, SRMR = 0.031, CFI = 0.998, TLI = 0.996 and RMSEA = 0.039. Thus, the nationality of the judges was not a significant factor in predicting the gymnasts’ execution scores (β = -0.008, p = 0.297) and overall results. The individual skill level of the gymnasts, particularly the difficulty value of the vault element, was the most important predictor of the overall ranking in the qualification event (β = -63.757, p < 0.001) and of the probability of qualifying for the final (β = 0.226, p = 0.001). The findings of this study reveal no empirical evidence of bias in gymnastics judging at an international competition. In the MAG vault event, the gymnast’s skill level, especially the difficulty value of the element, is the most crucial factor in determining the ranking outcome of the event. The implications for research and theoretical development are discussed.